Check vocabulary for FCE - Wyatt, Rawdon (Macmillian, 2008)
This workbook features a range of activities to help students learn and revise vocabulary for the First Certificate Exam. Using exercises, word games, puzzles and quizzes, the book covers both general and topic-specific vocabulary as well as grammar, comprehension and spelling.